UJI KUALITATIF BAHAN PENYUSUN SEDIAAN MIKROSFER BSA DENGAN KITOSAN DAN NA-TPP - Anggai, Rifka Anggraini; Mo’o, Faradila Ratu Cindana (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
This study aims to evaluate the qualitative characteristics of the components used in a protein delivery system based on microspheres, namely Bovine Serum Albumin (BSA), chitosan, sodium tripolyphosphate (Na-TPP), and maltodextrin, through organoleptic examination, Fourier Transform Infrared Spectroscopy (FTIR), and Differential Thermal Analysis (DTA). Organoleptic observations confirmed that all materials met standard physical characteristics as described in recent literature. FTIR spectra of BSA revealed the presence of amide I and II bands, indicating the preservation of its secondary protein structure. Chitosan exhibited functional groups capable of forming ionic crosslinks with TPP, essential in microsphere formation. The FTIR spectrum of TPP showed characteristic P=O and P–O–P absorption bands, confirming its role in ionic gelation. Maltodextrin displayed hydroxyl and carbonyl groups, supporting its function as a stabilizer in the formulation. DTA results demonstrated that all materials possess adequate thermal stability to withstand the formulation process. These findings suggest that the combination of BSA, chitosan, Na-TPP, and maltodextrin is compatible and effective in developing a stable microsphere-based protein delivery system, both in terms of chemical structure and thermal behavior.